Supply chain decision making in chemical industries using Analytical Hierarchy Process (AHP) a palm oil industry case study - Fathin, Idros (2013)
Nowadays, more development was done in all work fields to ensure they meet the customers need and market demand. Thus, supply chain was one thing that industries usually raised in their development plan in order to improve their process. The decision making supply chain was very important in industries to improve industry economies and flexibility of the process that was used. Therefore, in this study the development decision making of problem of supply chain at Felda Palm Industres Sdn. Bhd at Kilang Sawit Lepar Hilir in order to get the best alternatives by using Analytical Hierarchy Process (AHP) method was determined. Based on the analyses and results obtained, by introducing the high standard quality of selection of oil palm fresh fruits bunch the crude palm oil produced was followed the quality specification required.